PENGGANTIAN TEPUNG IKAN DENGAN TEPUNG KEONG MAS PADA LEVEL BERBEDA DALAM RANSUM TERHADAP PERFORMANS DAN KARKAS ENTOK - I W., TAMI; MASTIKA, I M.; NURIYASA, I M. (Majalah Ilmiah Peternakan; Vol 20 No 3 (2017): Vol 20, No 3 (2017), 2017)
An experiment was conducted on the replacement of fish meal with golden snails meal at different level on performance and carcass of muscovy ducks. A randomized complete block design (RCBD), with five treatments and four replications was used in this study so in other words there were 20 experiments unit conducted. Muscovy ducks were given diet using 15% fish meal as a control diet (R0), the replacement of 25% fish meal with golden snails meal (R1), the replacement of 50% fish meal with golden snails meal (R2), replacement 75% fish meal with golden snails meal (R3) and 100% replacement of fish meal with golden snails meal (R4). Meal Rations and drinking water are provided adlibitum. The results of the experiment showed that there was no significant difference (P>0.05) among in five treatments on the performances and carcass of muscovy ducks. The results also showed Muscovy duck given diet 75% replacement of fish meal with golden snails meal (R3) produced the highest performance and carcass. Based on the results of this experiment it was concluded that the replacement of fish meal with golden snails meal up to 100% did not affect performance and carcass of muscovy ducks.